PENYUSUNAN RENSTRA DESA WISATA BUNGA PADA KAWASAN EKOWISATA SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA JETIS KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Miftah Arifin; Yanto Yanto (Journal of Dedicators Community, 2017)
AbstractRegional policies on the development of Jetis as "tourism village flower", must continue to be developed because it can provide reciprocal benefits for humans and the environment. Unfortunately, the management concept of "tourist village built environment interest" in ecotourism in Jetis, not to apply the principle of participation-partnership between government and society, as well as the concept of the relationship between society and the environment. This activity is done by assisting the Village with facilitation techniques, so that the public is able to apply management "Tourism Village of Flowers" independently, through the Strategic Plan. As a result, synergy partnership between government and community is key to accelerating the success of ecotourism programs of interest for the welfare of society.Keywords: Strategic Plan for the Village, "Tourism Village of Flowers", Ecotourism, Welfare AbstrakKebijakan pengembangan Desa Jetis sebagai kawasan lingkungan desa wisata bunga, harus terus dikembangkan karena dapat memberikan manfaat timbal balik bagi manusia dan lingkungan. Sayangnya, konsep pengelolaan lingkungan binaan desa wisata bunga pada kawasan ekowisata di Desa Jetis, belum menerapkan prinsip partisipasi-kemitraan antara pemerintah dan masyarakat, maupun konsep hubungan antara masyarakat Desa Jetis dengan lingkungannya. Pengabdian ini berupa pendampingan agar masyarakat mampu secara mandiri menerapkan tata kelola Desa Wisata Bunga, melalui penyusunan Renstra Desa. Hasilnya, sinergitas kemitraan antara pemerintah dan masyarakat adalah kunci untuk mempercepat keberhasilan program ekowisata bunga demi kesejahteraan masyarakat.Kata Kunci: Renstrades, Desa Wisata Bunga, Ekowisata, Kesejahteraan.